Reply to Comment on The effect of a spectral filter on visual quality in patients with an extended-depth-of-focus intraocular lens - Łabuz, Grzegorz; Auffarth, Gerd U.; Özen, Aydin; van den Berg, Thomas J. T. P.; Yildirim, Timur Mert; Son, Hyeck Soo; Khoramnia, Ramin (American journal of ophthalmology, 2020)
We present the case of a 36-year old Curschmann-Steinert myotonic dystrophy patient with posterior subcapsular cataract that we treated with unilateral implantation of an extended depth of focus intraocular lens to address his wish for spectacle independence at far and intermediate distance. - The patient underwent phacoemulsification with subsequent implantation of the AcrySof IQ Vivity IOL (Alcon, Fort Worth, TX, USA) in his left eye. Uncorrected distance visual acuity (UDVA) on the left eye increased from +0.40 logMAR preoperatively to −0.12 logMAR at 3 months postoperatively. At the three months follow-up distance corrected intermediate visual acuity (DCIVA) at 80 cm distance was −0.08 logMAR and DCIVA at 66 cm distance was 0.14 logMAR for the left eye. The defocus curve showed a functional defocus of 2.0 diopters at 0.2 logMAR or better, corresponding to the extended depth of focus. Dysphotopsia evaluation with a Halo & Glare simulator (Eyeland-Design Network GmbH, Vreden, Germany) revealed a very low level of photic phenomena. - Unilateral implantation of a new generation, non-diffractive extended depth of focus IOL was well tolerated and provided good functional results for far and intermediate distances. The patient reported a very low level of photic phenomena.